Unusual finding of two filamentous fungi in a contact lens-related keratitis. Issue 2 (12th February 2021) - Tendo, Chris; Shahin, Bayan; Welch, James
Abstract : This is a rare case report of two filamentous fungi in a patient with contact lens related keratitis. An early corneal scrape may be useful in detecting multiple causative pathogens and aiding management. The main learning point is to consider fungal infections in patients with atypical ulcer appearances, as prompt diagnosis may reduce the morbidity burden.